Variation of the double product in patients after acute myocardial infarction submitted to aspersion bath - Moreira, Samara Oliveira; Assis, Allan Peixoto de; Souza Alves Vieira, Victor Hugo; Marcellini, Paulo Sergio [UNESP]; Abreu e Silva, Renata Flcivia (Univ Federal Estado Rio De Janeiro, Programa Pos-graduacao & Enfermagem, 2018)
Objective: This study aims to measure the double product variation in patients with acute myocardial infarction submitted to an aspersion bath. Methods: This is an observational study, performed at the Coronary Unit of a referral cardiology hospital located in Rio de Janeiro city, Rio de Janeiro State, Brazil. Data collection was carried out by sampling aspersion baths of adult patients of both genres with medical diagnosis of acute myocardial infarction either with or without elevation of the ST segment, and submitted to aspersion bath. Results: The results showed an increase in the average value of the double product in all patients, but without statistical significance. Conclusion: The aspersion bath in the study sample is a safe practice.
Keywords: Aspersion bath; nursing; myocardial infarction; cardiovascular nursing